POTENSI PLTMH PADA SALURAN PRIMER BENDUNG SUNGAI PRAFI KABUPATEN MANOKWARI - Yulianus Rombe Pasalli (FMIPA Universitas Papua, 2009)
This research was conducted in order to provide data, information and the design of hydraulics potential-based PLTMH (microhydro power plant) of the Prafi rivers. It is expected that the work will contribute thinking and planning for the Manokwari Government and those concerned in microhydro power plant installation to tourism and camp areas. The research was carried out by measuring data on the hydraulics potentials of debit and head. Followed with site condition observation of the microhydro power of tourism and camp areas. The collected data were then analyzed as bases for the microhydro power design emphasizing on the civil work, mechanical work, and the electric installation for microhydro power.The results obtained were civil work design of microhydro power with designed debit of 0,455 m3/s, and 3 m head, and generated power of 10 kW. The civil work design include intake submerged with size 0,58 m x 0,65 m, trashrack size 0,68 m x 0,85 m, material from strip iron 3 mm x 30 mm, head race size 0,5 m x 0,91 m, from the couple of crevice stone, inclined 1:500, silt basins size 1,5 m x 2 m, depth 2 m, made of the couple of crevice stone. Spillway size 0,4 m x 1,8 m, spillways is made above turbine pool, turbine pool is planned from concrete with diameter 0,80 m depth 1 m, draft tube is used PVC pipe, kind: AW, thick grey, diameter 8 inch, tail race there are 2 kind of tail race, from crevice stone and and soil, power house is planed with size 4 m x 5 m, foundation: couple crevice stone, pool, slop and concrete ring balk, wall concrete brick, floor white floor tile and roof iron sheeting. The mechanical installation using by turbine Propeller Open Flume with electric power effectif 10 kW or the specific speed 927 (rpm, HP, m), speed 999,76 rpm, with total efficiency 74,6 %, the fulley diameter (Dpt) 262,5 mm, Turbine Speed (Nt) 1000 rpm, for electric installation using by generator induction AC generator 10 kW, 220/380 Volt, 50 Hz, speed 1500 rpm, 4 poles, cos φ 0,8, and efficiency 0,9.